KISARAN INANG PERONOSCLEROSPORA MAYDIS DAN PENGENDALIAN KIMIAWI PENYAKIT BULAI PADA JAGUNG - , MUHAMMAD DWIKY Y, Prof. Dr. Ir. Christanti Sumardiyono, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This reseach aims to study the host range of Peronosclerospora maydis the couse agent of downy mildew and to study the effect fungicide of fenamidone and propamokarb hydrochloride + fenamidone in suppressing the development on downy mildew on corn. Weeds used in this reaseach was Cynodon dactilon, Echinocloa colona, Panicum repens, Cyperus rotundus, Cyperus kylingia and plants such as Pennisetum purpereums and Coix lacryma-jobi. Each weeds and plants consisted of 5 as replicates, each consisting of 5 plants. Inoculation was done by insert a piece of corn leaf that showed downy mildew symptoms to test plant leaf. Wet cotton to retain the moisture. The result showed that C. lacryma-jobi could use as alternate host of P. maydis. P.maydis chemical control was done in the field by seed dressing method. Fungicides used were fenamidone fungicide dose of 2 ml / kg, 4 ml / kg, 8 ml/kg , 16 ml / kg, 32 ml / kg, propamokarb hydrochloride + fenamidone with dose of 5 ml/kg, 10 ml / kg, 20 ml / kg, 40 ml / kg, 80 ml / kg and dimetomorf 4.5 ml / kg for comparison. Inoculation was done at 7th day after planting and observation at 7th day after inoculation. The result showed that all fungicide could not suppress the development of downy mildew of corn.